2022
DOI: 10.1007/s00395-022-00938-3
|View full text |Cite
|
Sign up to set email alerts
|

Negative interaction between nitrates and remote ischemic preconditioning in patients undergoing cardiac surgery: the ERIC-GTN and ERICCA studies

Abstract: Remote ischaemic preconditioning (RIPC) using transient limb ischaemia failed to improve clinical outcomes following cardiac surgery and the reasons for this remain unclear. In the ERIC-GTN study, we evaluated whether concomitant nitrate therapy abrogated RIPC cardioprotection. We also undertook a post-hoc analysis of the ERICCA study, to investigate a potential negative interaction between RIPC and nitrates on clinical outcomes following cardiac surgery. In ERIC-GTN, 185 patients undergoing cardiac surgery we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…For a considerable period, it has been recognized that transient hypoxic or ischemic preconditioning, remote ischemic preconditioning, and chronic hypoxia exposure offer protection to the heart against acute I-R injury in animals. Recent clinical trials have shown the limited improvement effect of transient limb remote ischemic preconditioning on clinical outcomes of surgical patients (3)(4)(5)(6)(7). Nonetheless, there are still doubts as to whether other hypoxic or ischemic methods can produce clinically significant myocardial protective effects.…”
Section: High-altitude Adaptation and Myocardial Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a considerable period, it has been recognized that transient hypoxic or ischemic preconditioning, remote ischemic preconditioning, and chronic hypoxia exposure offer protection to the heart against acute I-R injury in animals. Recent clinical trials have shown the limited improvement effect of transient limb remote ischemic preconditioning on clinical outcomes of surgical patients (3)(4)(5)(6)(7). Nonetheless, there are still doubts as to whether other hypoxic or ischemic methods can produce clinically significant myocardial protective effects.…”
Section: High-altitude Adaptation and Myocardial Protectionmentioning
confidence: 99%
“…Clinical practice does not allow for the application of many short-term pretreatment techniques, such as hypoxic or myocardial ischemic preconditioning, which significantly reduce myocardial I-R injury in animal experiments ( 2 ). Remote ischemic preconditioning has also been confirmed to be cardioprotective in animal studies, nonetheless, the results of several clinical studies have generated controversy ( 3 7 ). In a multicenter randomized clinical trial involving adult patients underwent cardiac surgery, there was no significant difference in the incidences of primary end point between the remote ischemic preconditioning group (14.3%) and the control group (14.6%) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nitroglycerin administration in cardioplegia solution increased NO levels and decreased troponin T levels in CABG patients [208]. In contrast, treatment with glyceryl trinitrate did not affect cardiac troponin T levels and even abrogated the cardioprotective effect of RIPC in cardiac surgery patients [209]. Taken together, NO donors seem promising in protecting the heart via the vasculature during CPB; however, it should be taken into account that most NO donors have platelet inhibitory properties and might therefore have clinical consequences in terms of postoperative bleeding [210].…”
Section: Oxidative Stressmentioning
confidence: 89%
“…Despite a substantial amount of preclinical data assessing the biological or pathological process of bowel RI [ 19 , 20 ], no clinical studies have been performed to date. Unlike in the field of myocardial [ 40 ] or cerebral ischemia [ 41 ], this significant gap between fundamental research and clinical practice is common in the field of mesenteric ischemia. Of course, AAMI is rare compared to ischemia in other organs [ 42 ], but more probably, this can be explained by the focus on bowel resection in historical surgical series [ 43 ].…”
Section: Discussionmentioning
confidence: 99%